Arabidopsis meiotic crossover hot spots overlap with H2A.Z nucleosomes at gene promoters - Choi, K; Zhao, X; Kelly, K; Venn, O; Higgins, J; Yelina, N; Hardcastle, T; Ziolkowski, P; Copenhaver, G; Franklin, F; Mcvean, G; Henderson, I (2013)
PRDM9 directs human meiotic crossover hot spots to intergenic sequence motifs, whereas budding yeast hot spots overlap regions of low nucleosome density (LND) in gene promoters. To investigate hot spots in plants, which lack PRDM9, we used coalescent analysis of genetic variation in Arabidopsis thaliana. Crossovers increased toward gene promoters and terminators, and hot spots were associated with active chromatin modifications, including H2A.Z, histone H3 Lys4 trimethylation (H3K4me3), LND and low DNA methylation. Hot spot-enriched A-rich and CTT-repeat DNA motifs occurred upstream and downstream, respectively, of transcriptional start sites. Crossovers were asymmetric around promoters and were most frequent over CTT-repeat motifs and H2A.Z nucleosomes. Pollen typing, segregation and cytogenetic analysis showed decreased numbers of crossovers in the arp6 H2A.Z deposition mutant at multiple scales. During meiosis, H2A.Z forms overlapping chromosomal foci with the DMC1 and RAD51 recombinases. As arp6 reduced the number of DMC1 or RAD51 foci, H2A.Z may promote the formation or processing of meiotic DNA double-strand breaks. We propose that gene chromatin ancestrally designates hot spots within eukaryotes and PRDM9 is a derived state within vertebrates. © 2013 Nature America, Inc. All rights reserved.